REAKTUALISASI PENDIDIKAN NILAI BERBASIS KEARIFAN LOKAL (Studi Budaya Langgam Syahadat Kures padaTradisi Sekaten di Surakarta) - Lila Pangestu Hadiningrum (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2018)
This research departs from the phenomenon of the increasingly eliminated elements of local culture in society, the issue of fading diversity and the increasing number of hate speech on social media. One of the causes is the flow of modernization and globalization of all aspects of life including tradition and culture. This study aims to re-actualize value education in Islamic culture and local wisdom in the Sekaten tradition in Surakarta in the present context. This study uses qualitative methods with a phenomenological approach. The results of this study indicate that the religious value of the Shah of Creed in the Sekaten tradition invites the community to worship, know God and the Messenger of Allah Rasulullah S.A.W through its nature and at the end of the style invites us to pray. In addition to religious values, in the Sekaten tradition, there is a social value education in the form of mutual cooperation and harmony and psychological values that invites us to know their nature and nature. The implementation of culture-based value education and local wisdom in the syahadat kures style in the Sekaten ritual requires human beings who are virtuous and devoted, have noble manners, the spirit of working, togetherness, good deeds and being able to put their human nature in balance between life in the world and the hereafter according to Islamic teachings. Culture-based value education and local wisdom become reinforcement so that humans become the generation of kaffah learners (insan kamil) intrinsically through the synergy of all elements (society, educators and parents).